Evaluation of Scar18 Marker Linked to B-Carotene for Early Screening of Mango (Mangifera indica L.) Progenies - Wardiyati, Tatik; Arumingtyas, Estri Laras; Roviq, Mochammad (AGRIVITA, Journal of Agricultural Science, 2010)
A breeding program of Mango (Mangifera indica) was organized by a team of Brawijaya University since 2006 by cross pollination between Arumanis 143 (green skin) with yellow skin cvs. of Carabao, Haden, Podang and Swarnarika in vice versa. As early identification a molecular evaluation was conducted. Measurement were on carotene content, DNA analysis using PCR and sequencing. The result showed that mango cultivars having orange or yellowish skin contain carotene higher than those mango cultivar having green skin. SCAR18 marker as a sign on the presence of beta (B) locus in tomato was not related with the differences of beta carotene accumulation in those manggo cultivars. SCAR18 marker that was amplified in mango produced specific amplimer of 320 bp in length. The similarity of SCAR18320 sequence obtaining by sequences alignment among five parental cultivars and 12 hybrids was up to 100%. SCAR18320 sequences that were generated by SCAR18 markers as predicted beta (B) loci had no significant similarity with sequences database relating to beta (B) gene in NCBI. SCAR18320 match to 19 Ty3-gypsy retrotransposons and others sequences related transcriptional regulator in more dissimilar sequences (discontiguous megablast) category.Keywords: SCAR18, ? carotene, skin color, Mangifera indica